Deletion of admB gene encoding a fungal ADAM affects cell wall construction in Aspergillus oryzae. Issue 5 (4th May 2017) - Kobayashi, Takuji; Maeda, Hiroshi; Takeuchi, Michio; Yamagata, Youhei
Abstract: Mammals possess a unique signaling system based on the proteolytic mechanism of a disintegrin and metalloproteinases (ADAMs) on the cell surface. We found two genes encoding ADAMs in Aspergillus oryzae and named them admA and admB . We produced admA and admB deletion strains to elucidate their biological function and clarify whether fungal ADAMs play a similar role as in mammals. The ∆admA∆admB and ∆admB strains were sensitive to cell wall-perturbing agents, congo red, and calcofluor white. Moreover, the two strains showed significantly increased weights of total alkali-soluble fractions from the mycelial cell wall compared to the control strain. Furthermore, ∆admB showed MpkA phosphorylation at lower concentration of congo red stimulation than the control strain. However, the MpkA phosphorylation level was not different between ∆admB and the control strain without the stimulation. The results indicated that A. oryzae AdmB involved in the cell wall integrity without going through the MpkA pathway. Abstract : :